Alternative choosing problem based learning in veterinary education - Şule OSMANAĞAOĞLU (Eurasian Journal of Veterinary Sciences)
All over the world, In the veterinary medicine, Problem Based Learning (PBL), for the first time implemented used in medical education at the beginning years of 1950 in North America. In the last years faculties of veterinary medicine, implemented same educational details revolutions or PBL in their training. In this article, it is aimed to tell what is PBL, the reason of using it increasingly in veterinary medicine education, advantages and disadvantages of it and in addition, the frame of using force in approaching to learning and teaching.